Integrated HOMER Pro–AHP Optimization of Standalone PV–BESS for Sustainable Household Electrification on Remote Islands - Syaifa Laila Sany; Christian Harito (Politeknik Siber Cerdika Internasional, 2026)
Background: Remote islands in Indonesia continue to experience limited access to reliable electricity due to geographical isolation and the lack of grid infrastructure. Batun Island in East Belitung Regency currently depends on diesel generators, resulting in high operational costs, fuel transportation challenges, and environmental concerns. Objective: This study aims to evaluate the feasibility and determine the optimal configuration of a standalone Solar Photovoltaic (PV) system integrated with a Battery Energy Storage System (BESS) to meet household electricity demand. Methods: A quantitative approach was employed by integrating HOMER Pro techno-ecoomic simulation with the Analytical Hierarchy Process (AHP) for multi-criteria decision-making. Four alternative PV–BESS configurations were evaluated based on technical, economic, environmental, regulatory, socio-cultural, and risk criteria. Results: The simulation results showed that all configurations were technically capable of supplying the estimated daily electricity demand of 89.99 kWh with a 100% renewable energy contribution. Among the evaluated alternatives, the 50 kWp PV and 200 kWh BESS configuration achieved the highest preference score of 0.889, with an AHP consistency ratio of 0.070, indicating reliable decision-making. This configuration also achieved the lowest NPC (USD 158,577) and LCOE (USD 0.37/kWh). Conclusion: The findings demonstrate that integrating HOMER Pro and AHP provides a comprehensive framework for optimizing standalone renewable energy systems and supports sustainable rural electrification planning for isolated islands in Indonesia.